#TITLE_ALTERNATIVE# - FARADHIMU ( NIM 15311036 ), TITO
In Indonesia, the management of clean water become state authority which responsibility is handed over to local government called the Drinking Water Regional Company (PDAM). Based on the districts data from PDAM, the service level in Bandung was 72.73% (PDAM, 2014). Unserved communities use alternative sources of water such as ground water and surface water. In addition, the performance of the PDAMÃ‚Â’s service that has not been able to provide water continuously give impact on the emergence of alternative solutions for communities both PDAM user and non PDAM user by the widespread use of household water storage system. With the risk of contamination when the water is stored, the water quality in water storage system should be checked based on microbiological parameters.Water samples were examined came from 70 houses with 2 different types of stored water in various water storage systems. Based on obervation, it was known that both PDAM users (21 respondents or 60%) and non PDAM users (15 respondents or 43%) prefer to choose water tank as water storage facilities. Based on microbiological analysis, it was known that both water samples from PDAM which have been stored in 4 storage facilities (346 MPN/100 ml dan 170 MPN/100 ml) and water samples from non PDAM which have been stored in 5 storage facilities (1018 MPN/100 ml dan 542 MPN/100 ml) have had average MPN value of total coliform and E.coli which were not in accordance with microbiological parameters from Ministry of Health Requirement No.492 of 2010 about Requirement of Drinking Water Quality so that it could be concluded that fecal contamination has been occured to stored water.